Analysis of Community-Based Tourism (CBT) Sustainability in Karedok Tourism Village, Jatigede District, Sumedang Regency - Raynaldi, Rizki; Malihah, Elly; Andari, Rini (Media Wisata, 2024)
Community-based tourism is seen as an alternative approach to tourist development due to its emphasis on the active participation of local communities and their potential contribution to its growth. The development of tourist villages is the manifestation of this concept, where local communities can effectively harness the natural resources, cultural assets, and human resources for the benefit of tourists, with the aim of positively impacting the community's economy. Karedok Village in Sumedang Regency has many tourism potentials, although the local community and village government have not effectively taken advantage of these potentials, resulting in a lack of economic benefits from the tourism context. This research tries to evaluate the extent to which the principles of sustainability in Community-based tourism have been implemented in the management of the Karedok Tourism Village. It will examine the five key principles of sustainability, namely economic, social, cultural, environmental, and political sustainability, using a descriptive-qualitative methods. The analysis findings indicate that the implementation of environmental and cultural sustainability principles has been successful. However, the principles of economic, social, and political sustainability have not been effectively implemented. This is reflected from the limited community participation, which impacts the progress of the sustainable tourism development.